Arthroscopic labral repair with all-suture anchors: a magnetic resonance imaging retrospective study with a 2.5-year follow-up - Federico Sacchetti; Martina Di Meglio; Nicola Mondanelli; Nicola Bianchi; Vanna Bottai; Federico Cartei; Fabio Cosseddu; Rodolfo Capanna; Stefano Giannotti (Medicinski glasnik, 2020)
Aim: To evaluate radiological and clinical outcomes of a case series of patients affected by glenohumeral instability (Bankart lesion) or superior labrum tear from anterior to posterior (SLAP) lesions treated by arthroscopic repair using all-suture anchors. Methods: Patients were operated by a single surgeon at a single Institution. Exclusion criteria were chondral lesions of the glenoid, rotator cuff lesions, previous surgery at the index shoulder, or a bony Bankart lesion. Position and numbers of anchors used depended on the dimension and type of lesion. The DASH (Disability of the Arm, Shoulder and Hand) and Constant scores were used for subjective and clinical evaluation at follow-ups (FUs); also, at 1-year FU, MRI scan was obtained to evaluate bone reaction to the implanted devices. Results: Fifty-four patients were included. A mean of 2.7 devices per patient (145 in total) were implanted. Mean FU was 30 (range 12 - 48) months. No patient reported recurrent instability, nor hardware-related complications were registered. MRI analyses showed that 119 (82%) implants did not alter surrounding bone (grade 0), 26 (18%) implants were surrounded by bone oedema (grade 1), while no bone tunnel enlargement nor a bone cyst (grade 2 or 3, respectively) were registered. Conclusion: This study confirmed the efficacy and safety of a specific all-suture anchor system in the arthroscopic repair of the glenoid labrum for glenohumeral instability or a SLAP lesion. In the short- and mid-term period, these devices were associated with good clinical and radiological outcomes without clinical failures or reaction at bone-device interface.
Keywords: Bankart lesion; bone-implant interface; hardware complication; shoulder; SLAP lesion